Pendekatan Fuzzy Servqual Untuk Mengevaluasi Tingkat Kepuasan Pasien di Praktik Dokter Karunia - Lina Rosina Limbong; Entin Sutinah; Nani Agustina (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2024)
Measuring patient satisfaction is one of the main indicators of measuring the quality of service in health facilities. Health service providers have difficulty measuring patient satisfaction, problems that are often complained about based on patient perceptions include late arrival of doctors at the clinic, lack of toilet cleanliness, long examination times, and the attitude of some nurses who are not friendly. The purpose of the study was to evaluate the level of satisfaction of patients who were treated at the Karunia Doctor's Practice using the Fuzzy Servqual method. Service quality was analyzed through five dimensions in the Servqual framework, namely tangible evidence, reliability, responsiveness, assurance, and empathy. The results of the study showed that the gap value of the five dimensions was negative, indicating that the quality of service provided did not meet the expectations of patients who were treated at the Karunia Doctor's Practice. The dimension with the highest gap value was tangible evidence with a value of -0.77, while the lowest gap value was in the reliability dimension. Thus, it can be concluded that the tangible evidence dimension requires special attention to improve service quality.